2023
DOI: 10.1038/s41467-023-38720-1
|View full text |Cite
|
Sign up to set email alerts
|

Structures of human SGLT in the occluded state reveal conformational changes during sugar transport

Abstract: Sodium-Glucose Cotransporters (SGLT) mediate the uphill uptake of extracellular sugars and play fundamental roles in sugar metabolism. Although their structures in inward-open and outward-open conformations are emerging from structural studies, the trajectory of how SGLTs transit from the outward-facing to the inward-facing conformation remains unknown. Here, we present the cryo-EM structures of human SGLT1 and SGLT2 in the substrate-bound state. Both structures show an occluded conformation, with not only the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…For instance, non-LeuT-fold TMs −1 and 13 of SGLT may limit TM1a swinging (Figure 5F). TM13 of the human homologs SGLT1 and SGLT2 binds to MAP17, an essential subunit for hSGLT2 glucose uptake activity that promotes cell surface expression 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, non-LeuT-fold TMs −1 and 13 of SGLT may limit TM1a swinging (Figure 5F). TM13 of the human homologs SGLT1 and SGLT2 binds to MAP17, an essential subunit for hSGLT2 glucose uptake activity that promotes cell surface expression 26 .…”
Section: Discussionmentioning
confidence: 99%
“…MAP17 co-expression enhances hSGLT2 activity without altering hSGLT2 expression on the cell membrane 19 . However, recent surface labeling experiments using antibodies against the extracellular domain of hSGLT2 have demonstrated that MAP17 is essential for robust surface hSGLT2 expression 34 . Although MAP17 is anticipated to induce a structural change in the active state of hSGLT2 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…The carriers are proteins that differ by substrate specificity, distribution, and regulatory mechanisms. Uniporters are sodium-independent, transporting glucose across the plasma membrane by facilitated diffusion (GLUTs and SWEETs) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Symporters are responsible for active glucose transport against its concentration gradient; they are sodium-dependent glucose cotransporters (SGLTs) [1]. They complement pancreatic hormones (insulin and glucagon) in maintaining sugar homeostasis through blood glucose level regulation.…”
Section: Introductionmentioning
confidence: 99%